2008
DOI: 10.1007/978-3-540-92185-1_54
|View full text |Cite
|
Sign up to set email alerts
|

On Pure and (Approximate) Strong Equilibria of Facility Location Games

Abstract: Abstract. We study social cost losses in Facility Location games, where n selfish agents install facilities over a network and connect to them, so as to forward their local demand (expressed by a non-negative weight per agent). Agents using the same facility share fairly its installation cost, but every agent pays individually a (weighted) connection cost to the chosen location. We study the Price of Stability (PoS) of pure Nash equilibria and the Price of Anarchy of strong equilibria (SPoA), that generalize p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 18 publications
(76 reference statements)
1
11
0
Order By: Relevance
“…The agent tries to minimize his individual cost; it consists of the (weighted) distance of i from v and a fair share of the facility installation cost at v. Facility installation cost at v is shared evenly among all agents having chosen v, or proportionally to their demand weight in case of weighted agents. In this paper we study pure Nash and strong equilibria (PNE and SE) of the described facility location game, and improve or extend previous results [1,2]. We prove a super-polynomial lower bound on the complexity of the Iterative Best Response algorithm for finding PNE, and analyze a polynomial-time algorithm for finding approximate PNE on metric networks.…”
Section: Introductionmentioning
confidence: 54%
See 4 more Smart Citations
“…The agent tries to minimize his individual cost; it consists of the (weighted) distance of i from v and a fair share of the facility installation cost at v. Facility installation cost at v is shared evenly among all agents having chosen v, or proportionally to their demand weight in case of weighted agents. In this paper we study pure Nash and strong equilibria (PNE and SE) of the described facility location game, and improve or extend previous results [1,2]. We prove a super-polynomial lower bound on the complexity of the Iterative Best Response algorithm for finding PNE, and analyze a polynomial-time algorithm for finding approximate PNE on metric networks.…”
Section: Introductionmentioning
confidence: 54%
“…. ) was shown in [2], even for the non-metric weighted case. Nguyen Kim [12] showed that PNE do not always exist for metric facility location games with weighted agents.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations